2019
DOI: 10.1177/0093854819896844
|View full text |Cite
|
Sign up to set email alerts
|

Adversity, Mental Health, and Substance Use Disorders as Predictors and Mediators of Rule Violations in U.S. Prisons

Abstract: This study explores how typologies of adversity and mental health/substance use disorders impact rule violations during incarceration. Data come from the 2004 cross-sectional Survey of Inmates in State and Federal Correctional Facilities (SI-SFCF). Logistic regression and structural equation modeling were used for analysis. Results link history of adverse experiences to rule violations during incarceration and demonstrate how mental health and substance use disorders mediate this relationship. Incarcerated peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
9
0
2
Order By: Relevance
“…According to Henry 11 , the existence of dysfunctional behaviours as a response to difficulties in social adjustment to the prison setting leads to breaches of prison regulations, which take mainly take two forms: drug offences, consisting of possession, trafficking and consumption; and serious offences, such as verbal and/or physical aggression against other inmates or the other persons with whom they interact, possession of arms, attempts to escape, etc.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Henry 11 , the existence of dysfunctional behaviours as a response to difficulties in social adjustment to the prison setting leads to breaches of prison regulations, which take mainly take two forms: drug offences, consisting of possession, trafficking and consumption; and serious offences, such as verbal and/or physical aggression against other inmates or the other persons with whom they interact, possession of arms, attempts to escape, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Henry 11 reached the conclusion that inmates with mental health issues and drug disorders run a higher risk of breaking prison rules, with a particular risk of committing serious offences related to inadequate interactions with the prison social climate ( Figure 4 ). This risk is even greater amongst inmates who suffer from an acute mental illness and adverse life experiences such as recidivism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abusive use of drugs in psychological patients is a prevalent issue that affects social and occupational performance of the individual [7]. Studies on abusive use of drug have shown that there is a direct relationship between abusive use of drugs and mental health [7,8]. Developing drug dependence hinders fulfillment of social, spiritual, and emotional roles of the user at social and family levels; which causes problems for the society and family [9].…”
Section: Introductionmentioning
confidence: 99%